(3fRgg GdSGeY aj GdYed HGdQHY GdLGeYs - (3Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, CHh GdMSf YdGA GdOjf, GdeYQha HGHf GdTGWQ,J (B777 (3g` s; (3GHf GdTGWQ , Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, YdGA GdOjf CHh GdMSf,J (B777 (3g` s ((3Ydi Hf eMeO Hf GdOdGei s)
(3ChdgG (B:s
(3HYO GdOjGLg (B: (3agPg QSGdg GNJUQJgG ef GdQSGdg GdJi cfJ hVYJgG GdeSeGg HJMag GdSGeY aiGdYed HGdQHY GdLGeY s
(3BNQgG (B:s
(3hEf cGf eWGdYg GcKQ aGQJaGYg ZQHi hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B79 - (3U(B99s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs